Growth, yield and fiber morphology of kenaf (Hibiscus cannabinus L.) grown on sandy BRIS soil as influenced by different levels of carbon - Hossain, Md. Delwar; Musa, Mohamed Hanafi; Jol, Hamdan; Abdul Hamid, Hazandy (Academic Journals, 2011)
The effects of carbon levels on plant growth, yield and fiber morphological properties are not available for kenaf that is considered as a potential source of low cost natural fiber and feedstock for energy production as well. A pot-culture experiment was conducted in shade house to determine the effects of carbon levels on plant growth, yield and fiber morphology of different kenaf varieties. The plants of five kenaf varieties were grown in pots containing sandy beach ridges interspersed with swales (BRIS) soil. Organic carbons at the levels of 0, 10, 20, 30 and 40 t ha-1were applied to pots using organic fertilizer. At harvest, stem diameter, plant height, leaf number, leaf area, plant components biomass, bast and core fiber yield and fiber dimensional properties were determined. Maximum growth, dry matter and fiber yield, and morphological characters were achieved at the carbon levels 20 t ha-1 but the values of these parameters decreased with additional increase in carbon levels. Among the varieties, HC2 had the highest plant height, leaf biomass, total dry matter and fiber yield. The longest bast fiber was observed in variety HC2. The variety G4 showed the widest fiber and higher lumen width among others. The bast fibers of all the kenaf verities were longer than core fiber. The core fiber was wider and higher in lumen width than the bast fiber. The above results keep a significant role and would be useful to select better varieties of kenaf for the purpose of making quality paper and paper products and to grow kenaf on BRIS soil with adequate yield and fibre quality using better management of organic carbon.